1996
DOI: 10.3354/meps136013
|View full text |Cite
|
Sign up to set email alerts
|

Migrations in an extreme northern population of Arctic charr Salvelinus alpinus:insights from otolith microchemistry

Abstract: Growth and migrations of Arctic charr from a Norwegian Arctic lake system were examined using structural and chemical characteristics of their otoliths as indicators of physiological and habitat characteristics. Measurements of otolith strontium/calcium concentration ratios by wavelength dispersive electron microprobe clearly revealed salinity migrations and provided a life history profile for individual fish. There was wide range in the age at first seaward migration (4 to 13 yr; mean 6.7 yr). Sr/Ca concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…Climate variations can thus inflict high mortality on Arctic anadromous populations. By microchemical analysis for Sr/Ca ratios in otoliths, Radtke et al. (1996) and Svenning (2001) found that individual charr abstained from migration in some years inVårflusjøen (79°N) and Arkvatn (80°25′N) further north on Svalbard.…”
Section: Arctic Charr Salvelinus Alpinus (L)mentioning
confidence: 99%
“…Climate variations can thus inflict high mortality on Arctic anadromous populations. By microchemical analysis for Sr/Ca ratios in otoliths, Radtke et al. (1996) and Svenning (2001) found that individual charr abstained from migration in some years inVårflusjøen (79°N) and Arkvatn (80°25′N) further north on Svalbard.…”
Section: Arctic Charr Salvelinus Alpinus (L)mentioning
confidence: 99%
“…Consequently, the strontium:calcium ratio of the otolith records fish habitat, either salt water or fresh water, throughout the life of the fish. Radtke & Kinzie (1996) and Radtke et al (1996) have used this method successfully to document freshwater‐marine transitions.…”
Section: Otolith Analysismentioning
confidence: 99%
“…Consequently, trace elements incorporated into the otolith during formation can yield detailed chronological information about the environmental variation encountered by fish over their lifetime (e.g. Kalish, 1995;Radtke et al, 1996a;Campana, 1999;Ivany et al, 2000;Andrus & Crowe, 2002).…”
Section: Introductionmentioning
confidence: 99%